+0  
 
0
109
1
avatar

thank you 

 Dec 12, 2019
 #1
avatar+109064 
+1

                  3x^2  - 7x  -  6          (3x + 2) ( x - 3)             3x +  2

f(x ) =        ____________ =     _____________  =       _______       (1)

                  2x^2  - 5x  -  3          (2x + 1) ( x -3)              2x  +  1

 

 

The x coordinate of the   "hole"  can be  found as    x  - 3  = 0  ⇒   x  = 3

 

To find the y coordinate of the hole......sub  this x value into  (1)   and we have

 

3(3)  + 2              11

_______  =        ____ 

2(3) + 1                 7

 

So....the "hole" occurs at    (3, 11/7)

 

See the graph, here :

 

https://www.desmos.com/calculator/7mdt3lommd

 

 

cool cool cool

 Dec 12, 2019

9 Online Users